Rock of ages; - Robertson, Robbie (2009)
Any way you want it -- Beaver hunt -- Can't fight this feeling -- Cum on feel the noize -- Don't stop believin' -- Every rose has its thorn -- Final countdown -- Harden my heart -- Heat of the moment -- Heaven -- Here I go again -- High enough -- Hit me with your best shot -- I hate myself for loving you -- I wanna rock -- I want to know what love is -- Just like paradise -- Keep on loving you -- More than words -- Nothin' but a good time -- Oh Sherrie -- Renegade -- The search is over -- Shadows of the night -- Sister Christian -- To be with you -- Too much time on my hands -- Waiting for a girl like you -- Wanted dead or alive -- We built this city -- We're not gonna take it.